Comparative study of radiation dose measurement around 1921r source with manual calculation - Abdullah, Nazifah (2004)
The purpose this study is to measure dose around an HDR 1921r source in a vaginal-applicator. The dosimeters used were gafchromic film, and LiF Thermoluminescent dosimeter (TLD 100 chip). The manual calculation was carried out to compare the results with measurement. Gafchromic film was calibrating using 6MV photon beam, to obtain the relationship between absorbed dose and film response. In this study gafchromic film and LiF Thermoluminescent was setup in three different configurations. The remote after loading machines was programmed to send the source C921r) move through a cylinder to the programmed position and dwell time. The results showed that the manual calculation was higher than TLD and film dosimeter.